Accounting, auditing and governance for Takaful operations - Htay, Sheila Nu Nu. (Singapore : Wiley, 2012)
A comprehensive guide to current issues and practices in governance for Takaful and re-Takaful operations. As the global demand for Islamic insurance products increases, a thorough understanding of Takaful principles is vital for accountants, auditors, and leaders of companies offering these products. This book covers the basic accounting principles and practices of Takaful operations, including the segregation of assets, liabilities, income, and expenditures between the Takaful operator and participants; the setting aside of cash reserves for meeting outstanding claims and future claims; and the management of revenue and expenditure. Featuring extensive case studies from real-world situations, this book is the perfect primer for accounting students and practitioners unfamiliar with Islamic finance and Takaful operations. Written by experts from the International Islamic University Malaysia, the leading organisation in research in Islamic finance. Covers all the major accounting principles and practices. Based on real-world experience and packed with illustrative case studies. For practicing accountants and business leaders, this book offers a thorough education in Takaful operations while also serving as an excellent guide for undergraduate students and researchers.
Keywords: Insurance law (Islamic law); Insurance -- Accounting; LAW -- Administrative Law & Regulatory Practice; Insurance -- Accounting; Insurance law (Islamic law); Electronic books; Electronic books